2020
DOI: 10.3390/molecules25184296
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Identical Compounds and Organic Acids Ameliorate and Prevent the Damages Induced by an Inflammatory Challenge in Caco-2 Cell Culture

Abstract: Bioactive compounds, such as organic acids (OA) and nature-identical compounds (NIC), can exert a role in the protection of intestinal mucosa functionality due to their biological properties. The aim of this study was to understand the role of 2 OA (citric and sorbic acid) and 2 NIC (thymol and vanillin), alone or combined in a blend (OA + NIC), on intestinal barrier functionality, either during homeostatic condition or during an inflammatory challenge performed with pro-inflammatory cytokines and lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…But the complex nature of the colonization process requires a tailored combination of in vitro evidence combined in vivo data so the effects of these mixed antimicrobials can be understood and utilized as part of a One Health approach to improving animal health. Previously it has been suggested that combinations of antimicrobials, rather than single compounds, were more efficient in controlling bacterial infections 47 and our study demonstrates that synergistic effects can be also occur against parasitic infections in vitro and in vivo. Results suggest that mixtures of natural antimicrobials can: (1) modulate the host immune response, (2) reduce parasite-induced host oxidative events, and (3) alleviate clinical signs and growth inhibition associated with coccidiosis.…”
Section: Discussionsupporting
confidence: 66%
“…But the complex nature of the colonization process requires a tailored combination of in vitro evidence combined in vivo data so the effects of these mixed antimicrobials can be understood and utilized as part of a One Health approach to improving animal health. Previously it has been suggested that combinations of antimicrobials, rather than single compounds, were more efficient in controlling bacterial infections 47 and our study demonstrates that synergistic effects can be also occur against parasitic infections in vitro and in vivo. Results suggest that mixtures of natural antimicrobials can: (1) modulate the host immune response, (2) reduce parasite-induced host oxidative events, and (3) alleviate clinical signs and growth inhibition associated with coccidiosis.…”
Section: Discussionsupporting
confidence: 66%
“…Organic acids (e.g. citrus extracts) have been shown to reduce the generation of reactive oxygen species thereby preventing oxidative cell injury [ 34 ] and when used in combinations will restore TEER and improve cellular tight junctions [ 26 ]. The Auraguard-catalysed reduction in H 2 O 2 released by the infected MDCK cells was linked to the observed increased expression of the ZO-1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of zonula occludens-1 (ZO-1) and occluding expression was performed as previously described with small modifications [ 26 ]. Briefly, the exposed or infected MDCK cells were snap-frozen in liquid nitrogen until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the potential beneficial effects on epithelial cells of medium-chain fatty acids are not fully understood yet. Toschi et al (2020) reported also beneficial effects of citric acid on the epithelial barrier function and tight junction gene expression in vitro. Bacitracin is an antimicrobial agent, used to control NE in poultry.…”
Section: Introductionmentioning
confidence: 90%